AI adoption, technological readiness, and AI usability in sustainability accounting education: The moderating role of academic integrity - Tamara Adel Al-Maaitah; Khalid Ali Alduneibat; Sajead Mowafaq Alshdaifat; Rakan Alsarayreh; Ahmad Yahiya Ahmad Bani Ahmad; Areej Hijazin (Heritage and Sustainable Development)
This study investigates the influence of AI adoption tools, user readiness, and ease of use on sustainability accounting education in Jordanian public universities, moderated by academic integrity. As AI becomes increasingly integrated into university instruction, its influence on learning outcomes and ethics is paramount. Survey data from 384 instructors at 10 Jordanian public universities were analyzed with Smart PLS. The results show that AI implementation improves education in sustainability accounting by improving accessibility, effectiveness, and personalization. Usability greatly facilitates the adoption of AI, with increased student engagement by providing higher levels of involvement. Yet, as education in academic integrity encourages responsible and ethical AI use, it also creates challenges for adoption whenever regulations are perceived as overly limiting. These results highlight the importance of a balance between innovation and ethics and stress how institutions need to invest in adaptive policy infrastructures and digital literacy. The study contributes to theoretical understanding and practical guidance for policymakers and educators in AI-supported education.